The prevalence of lower urinary tract symptoms (LUTS) and its associated risk factors among male university students - Gan, Xinyi (2024)
Background: Lower Urinary Tract Symptoms (LUTS) arise from dysfunction in the bladder, urinary sphincter, urethra, or prostate and include voiding and storage symptoms. While more common in adult males, LUTS can affect anyone and is linked to risk factors like obesity, hypertension, and diabetes. Early diagnosis is vital for prevention and better outcomes. However, no studies have explored the prevalence and risk factors of LUTS among male university students in Malaysia.